Dried Culture Spots for Xpert MTB/RIF External Quality Assessment: Results of a Phase 1 Pilot Study in South Africa - Scott, L. E. (American Society for Microbiology, 2011)

(untitled)
Implementation of Xpert MTB/RIF requires quality assessment. A pilot program using dried culture spots (DCSs) of inactivated Mycobacterium tuberculosis is described. Of 274 DCS results received, 2.19% generated errors; the remainder yielded 100% correct Mycobacterium tuberculosis detection. The probe A cycle threshold (C(T)) variability of three DCS batches was ≤3.47. The study of longer-term DCS stability is ongoing.